Bouncing microdroplets on hydrophobic surfaces - Jamie McLauchlan; Jim S. Walker; Vatsal Sanjay; Maziyar Jalaal; Jonathan P. Reid; Adam M. Squires; Anton Souslov (Proceedings of the National Academy of Sciences, 2025)
Intuitively, slow droplets stick to a surface and faster droplets splash or bounce. However, recent work suggests that on nonwetting surfaces, whether microdroplets stick or bounce depends only on their size and fluid properties, but not on the incoming velocity. Here, we show using theory and experiments that even poorly wetting surfaces have a velocity-dependent criterion for bouncing of aqueous droplets, which is as high as 6 m/s for diameters of 30 to 50 μ m on hydrophobic surfaces such as Teflon. We quantify this criterion by analyzing the interplay of dissipation, surface adhesion, and incoming kinetic energy, and describe a wealth of associated phenomena, including air bubbles and satellite droplets. Our results on inertial microdroplets elucidate fundamental processes crucial to aerosol science and technology.